A U-Shaped Relationship Between Selenium Concentrations and All-Cause or Cardiovascular Mortality in Patients With Hypertension - Qiu-hong Tan (Frontiers in Cardiovascular Medicine, 2021)
Background: Given the antioxidant activity of selenium, it has been reported benefits for blood pressure control and hypertension prevention, but few studies have investigated the association between serum selenium with mortality in hypertensive population.Methods: All participants with hypertension aged ≥18 years at baseline were recruited from the National Health and Nutritional Examination Surveys (NHANES) 2003–2004, and followed for mortality through December 31, 2015. Subjects were categorized by quartiles of serum selenium (Q1: ≤124 μg/L, Q2: 125–135 μg/L, Q3: 136–147 μg/L, Q4: ≥148 μg/L). Multivariate Cox regression were implemented to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Restricted cubic spline analysis and two-piecewise linear regression were used to evaluate the relationship of serum selenium with mortality. Survival curves were used to depict cause-specific mortalities.Results: A total of 929 participants (52.53% were male) were eligible for the current study with the average age of 63.10 ± 12.59 years. There were 307 deaths occurred including 56 cardiovascular death events during the mean follow-up time of 121.05 ± 40.85 months. A U-shaped association was observed between serum selenium and all-cause or cardiovascular mortality. In fully adjusted model, comparisons among quartiles revealed that risks of all-cause [HR (95%CI), 0.57 (0.39–0.81)] and cardiovascular death [HR (95%CI), 0.33 (0.13–0.86)] were lower in Q3. The nadir mortality of all-cause and cardiovascular was occurred at the serum selenium level of 136 μg/L and 130 μg/L, respectively.Conclusion: Serum selenium concentration showed a U-shaped association with all-cause and cardiovascular mortality.